Pengelolaan ZIS di Desa Tinggar - Muhammad Fodhil; Nurus Silfiyana; Rudi Kristanto (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2021)
This study aims to find out the management of zis (zakat, infaq, and shodaqoh) in Tinggar Village. The approach method for the implementation of community service activities in the KKN-PPM scheme includes the method of lectures and discussions. The method used in this activity is to use the lecture method through the form of ngobras (nice chat) through the form of socialization and held ngobras (chat) sharia economy how to manage the right ZIS. Community service activities in the KKN-PPM scheme will be carried out optimal socialization in the management and development of ZIS. This activity supports tanfidiyah and Banom NU members to increase knowledge to manage ZIS properly and appropriately, increase tanfidiyah and Banom NU members to share with fellow human beings, especially the mustahiks (poor people, converts, amyl, ibn sabil, riqab, gharimin and fisabilillah), and maintain economic stability in tinggar village kec. Bandar kedungmulyo kab. Jombang.